Empowering Science Education with Google Sites: Development and Evaluation of Differentiated Learning Media for Middle School Using the ADDIE Model - Erayana Munthe; Sriadhi Sriadhi; Agus Junaidi (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: The rapid advancement of digital technology and the implementation of the Merdeka Curriculum in Indonesia have highlighted the need for differentiated learning to address the diverse needs of students. However, many classrooms still employ uniform teaching methods, which often fail to accommodate individual learning styles, particularly in science education.Aims: This study aimed to develop and evaluate differentiated learning media supported by Google Sites for the science topic “Classification of Living Things”, tailored to students' visual, auditory, and kinesthetic learning preferences.Methods: The research adopted the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Expert validation was conducted by specialists in content, media, and instructional design. The media was tested in three phases: individual, small-group, and field testing. Effectiveness was assessed by comparing the pretest and posttest scores between the experimental group and the control group using parametric statistical tests.Results: The developed media was rated as “Very Feasible” by experts, with average validation scores exceeding 89%. User testing also yielded highly positive feedback, with an average feasibility score of 88%. The experimental group achieved significantly higher post-test scores than the control group (p < 0.05), and the normalized gain score of 0.46 indicated moderate effectiveness.Conclusion: Differentiated learning media supported by Google Sites is a feasible and effective tool for enhancing student learning outcomes in science education. Its integration supports personalized learning and aligns with the national curriculum reforms that emphasize student-centered instruction.